Generative Artificial Intelligence in Education and its Governance: Perspective of Copyright Law: - Mayana, Ranti Fauza; Santika, Tisni (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
As a domain of science and technology, Artificial Intelligence (AI) opened new horizons for education. Technologies change the ways we teach and learn. While Generative AI tools create new prospects for learning, several concerns also arise. Educators are worried that they cannot differentiate between the output of students' work and the output from AI and this will impact the discipline, originality, integrity, and ethics in such cases. In addition, the problem also potentially arises in the matter of the authorship of the works regarding Copyright Law.  This paper examines several legal issues of the utilization of Generative AI through the perspective of Copyright Law. This paper concludes several important points; First, although the framework of Indonesia’s copyright law is based on the principle of human authorship, the rapid development of Generative AI must be balanced with an accommodative legal framework, Second, it is particularly important to formulate a special provisions to guide the implementation concerning the utilization of copyrighted works as the input material for generative AI so that it will not harm the "legitimate interest of the author" in the limit of "normal exploitation of the work" and classified as fair use, Third, academics and administrators need to gain a better understanding of the promise and perils of generative AI, how it will likely impact education, and how it might best govern by encourage the school and universities to develop institutional policies and/or formal guidance concerning the use of digital technology and Generative AI for the future of education.